Textiles as national heritage : identities, politics and material culture : case studies from Uzbekistan, Kazakhstan, Algeria and Peru - Mentges, Gaby, 1952-; Shamukhitdinova, Lola; Korbik, Johanna; Fink, Jella; Adelt, Svenja; Sattler, Julia (Waxmann, 2017)
The edited volume discusses the role of textile heritage in realtion to the dynamics of nation building, cultural identity, politics, economy, and the globalization of markets. It was sparked by a research project investigating the role of textiles, textile design, and contemporary fashion in the post-Soviet societies of Central-Asia and also includes perspectives on similar developments in Algeria and Peru in order to question dichotomous narrations of modernity relations between textile cultures and heritage buliding, cultural property, and the concept of cultural heritage. Thus, this book intends to stimulate the ongoing debate about textile culture as national heritage or as means of nation building. --